Exploring diversity in PE teacher training: Immersive learning challenges & potentials - Haas, Silke; Besch, Julia (Current Issues in Sport Science, 2024)
The aim of teacher training in PE is to teach subject-specific content and to promote a reflective attitude. This is particularly important in preparation for inclusive physical education (Meier et al., 2017). Additional, research shows that videography is an effective tool for prospective and practicing teachers (e.g. Walshe & Driver, 2019). Immersive teaching methods such as VR-based learning scenarios could further strengthen such methods (Huang et al., 2023). Based on this, questions arise about the learning-effective design features of immersive methods regarding complex learning objectives in teacher training. This contribution will present a sports didactics seminar that focuses on teaching reflection within the framework of diversity-sensitive sports didactics and initial exploratory results in this regard. Thereby reflection is understood as a mental mediation between practical experience, professional knowledge, and teachers’ convictions (Leonard, 2022). The explorative evaluation focusses on the question whether the immersive experience of physical education can be used as a starting point for a reflection process among (prospective) teachers and if so how the immersion experience influences the students' ability to reflect sensu Leonard (2022) by confronting them with 360° instructional videos. A control group design is pursued (360° technology vs. videography). Firstly, standardized questionnaires are used to assess the students’ sense of immersion directly after watching the 360° video resp. standard video. A T-Test is used to analyse the difference in sense of presence and sense of immersion between the groups. The analysis reveals a significant difference between the groups in the sense of presence (t(77) = −4.78, p < .001) and in the sense of immersion (t(77) = -5.85, p < .001). The 360° group shows significantly higher values in both areas. Secondly, the students’ attitudes towards inclusive physical education are evaluated (Meier et al., 2017), the data show no differences between the groups (e.g. t(75) = -0.09, p = .93). In contrast, the depth of reflection indicates qualitative differences which will be discussed in the contribution (Hatton & Smith, 1995). These first results regarding the feelings of presence and immersion, as well as noticing situations and their relationships to each other, will be reported and insights into the immersive PE scenarios will be provided. References Hatton, N., & Smith, D. (1995). Reflection in teacher education: Towards definition and implementation. Teaching and Teacher Education, 11(1), 33-49. https://doi.org/10.1016/0742-051X(94)00012-U Huang, Y., Richter, E., Kleickmann, T., & Richter, D. (2023). Virtual reality in teacher education from 2010 to 2020. In K. Scheiter, & I. Gogolin (Eds.), Bildung für eine digitale Zukunft (pp. 399-441). https://doi.org/10.1007/978-3-658-37895-0_16 Leonard, T. (2022). Reflexionsregime in Schule und Lehrerbildung. Zwischen guter Absicht und transintentionalen Folgen. In C. Reintjes, & I. Kunze (Eds.), Reflexionsregime in Schule und Lehrerbildung (pp. 77–93). Verlag Julius Klinkhardt. https://doi.org/10.25656/01:25404 Meier, S., Ruin, S., & Leineweber, H. (2017). HainSL – Ein Instrument zur Erfassung von Haltungen zu inklusivem Sportunterricht bei (angehenden) Lehrkräften [HainSL — A testing instrument to assess attitudes of (trainee) teachers regarding inclusive physical education lessons]. German Journal of Exercise and Sport Research, 47(2), 161–170. https://doi.org/10.1007/s12662-016-0429-9 Walshe, N., & Driver, P. (2019). Developing reflective trainee teacher practice with 360-degree video. Teaching and Teacher Education, 78, 97-105. https://doi.org/10.1016/j.tate.2018.11.009